Contraception and Meeting the Reproductive Needs of Every Woman, Every Time - Nierengarten, Mary Beth (MD Conference Express, 2014)
In her inaugural speech at her swearing in as the 64th president of the American Congress of Obstetrics and Gynecology (ACOG) at the 2013 annual meeting, Jeanne A. Conry, MD, PhD, used the mantra “Every Woman, Every Time” to highlight the importance of addressing reproductive health in women at every opportunity. This article discusses the advantages of long-acting reversible contraceptives, best emergency contraception, transcervical sterilization, as well as evidence-based guidelines for contraceptive use.